Strategy To Improve Briguna Digital Sustainability Performance At Bank Bri In The Regional Area Of Central Java Province & Special Region Of Yogyakarta - Candra Setia Barkah; Ratna Lindawati Lubis (urn:multiple://2988-7828multiple.v3i84)
This study aims to formulate a strategy to improve the sustainability performance of BRIGuna Digital in the BRI Regional Office of Central Java and the Special Region of Yogyakarta (DIY), using a mixed methods approach. The research began with interviews and observations involving 23 purposively selected informants, consisting of BRI employees and active BRIGuna Digital users. Qualitative data were analyzed using SWOT and triangulation approaches and then used as the basis for developing a Likert-scale questionnaire. The questionnaire results were analyzed descriptively and used to construct the IFAS and EFAS matrices, which served as the foundation for formulating an adaptive and responsive strategy to enhance BRIGuna Digital's performance. The findings indicate that the main strengths lie in the integrated information system and branch network capabilities, while significant weaknesses are found in technical aspects and user outreach. The IFAS and EFAS results place the company in an aggressive strategy position. An SO (Strengths–Opportunities) strategy was selected, focusing on optimizing internal potential to seize external opportunities. The recommended strategy implementation includes targeting bonafide institutional clients, forming promotional partnerships with business partners, strengthening brand image through digital security, educating non-digital users, updating leads data with regional mapping, adjusting autodebit to salary schedules, tightening screening for payroll-switching debtors, and offering competitive interest rates with flexible tenors. This research provides strategic contributions to the development of sustainable performance in the national digital financial services sector